A broadband and low cross‐polarization balanced dual‐polarized cross quasi‐yagi antenna. Issue 3 (6th January 2021) - Zhao, Xi‐Bei; Wei, Feng; Shi, Xiao Wei
Abstract: A broadband balanced fed dual‐polarized cross quasi‐Yagi antenna with a compact size, low cross‐polarization, and good common‐mode (CM) suppressions is provided. The proposed antenna consists mainly of two balanced quasi‐Yagi antennas, which are vertical to each other. Balanced microstrip‐slotline feeding line structures are utilized to excite the two quasi‐Yagi antennas to achieve ±45° linear polarizations. A good end‐fire radiation in a broad bandwidth is achieved by introducing the directors above the dipoles of the cross quasi‐Yagi antenna. Meanwhile, a good wideband common‐mode (CM) suppression and low cross‐polarization levels are realized by the balanced microstrip‐slotline feeding line structure. Besides, superior DM transmission and CM suppression are achieved intrinsically, thereby simplifying the design procedure significantly. Finally, the balanced dual‐polarized antenna is fabricated to validate the feasibility of this design method. The measured dates show that the designed antenna characterizes broadband, high port isolation and CM suppression, low cross‐polarization levels and stable gain radiation.